Orthography and Time of the Epitaphs written by Simonas Daukantas for Simonas Lopacinskis (d. 1814) and Kotrynė Daukantienė (d. 1847) - Subačius , Giedrius (Senoji Lietuvos literatūra, 2024)
There are two known stone monuments with epitaphs, written by Simonas Daukantas in his own orthography: for a relative priest Simonas Lopacinskis (died in 1814) and for his mother Kotrynė Daukantienė (died in 1847). Analysis of Lopacinskis’s epitaph spelling proves that Daukantas inscribed the text of the gravestone approximately in 1838–1841 (24–27 years after the death of Lopacinskis). His mother’s epitaph is said to be compiled by Daukantas in the beginning of 1848. And graphochronological research reconfirms that this epitaph includes features characteristic to Daukantas orthography in about 1848–1850. Entire Lopacinskis’s epitaph was chiseled out in capital letters. Analysis shows, however, that most of the text written by Daukantas hand must have initially been rendered in lower case letters. And Daukantienė’s epitaph might have been chiseled out not directly from Daukantas’s handwritten note, but from the text first set in print. Daukantas spelled his mother’s last name DAU-KONTIENE with the digraph <on>, signifying her native dialectal diphthong [ọn]. Elsewhere at the time Daukantas preferred different digraph <ąn>, so the spelling with <on> might have been an important identity trait of his mother and of his entire family. Had Daukantas’s own signature in Lithuanian survived, it might have contained the same digraph <on> – Daukont’s or Daukontas.